2014
DOI: 10.1108/intr-05-2012-0100
|View full text |Cite
|
Sign up to set email alerts
|

Are personal innovativeness and social influence critical to continue with mobile commerce?

Abstract: Purpose – The purpose of this paper is to report a study investigating the impact of personal innovativeness in information technology (PIIT) and social influence on user continuance intention toward mobile commerce (m-commerce) in the USA. Design/methodology/approach – A survey was conducted among undergraduate and graduate mobile users in a regional university. Structural equation modeling procedures were deployed to analyse 323 valid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
226
3
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(267 citation statements)
references
References 88 publications
20
226
3
18
Order By: Relevance
“…Fan et al (2005) found that, compared with perceived ease of use and perceived usefulness, social influence had more impact on a user's acceptance of m-commerce. Lu (2014) found that, compared with perceived ease of use, perceived usefulness is more often identified as a mediator of social influence. Social influence has been found to be both a determinant (Lu 2014;Wei et al 2009) and an antecedent (Chan and Chong 2013;Sadia 2011) of m-commerce adoption.…”
Section: Factors Affecting Adoption Of M-commercementioning
confidence: 96%
See 2 more Smart Citations
“…Fan et al (2005) found that, compared with perceived ease of use and perceived usefulness, social influence had more impact on a user's acceptance of m-commerce. Lu (2014) found that, compared with perceived ease of use, perceived usefulness is more often identified as a mediator of social influence. Social influence has been found to be both a determinant (Lu 2014;Wei et al 2009) and an antecedent (Chan and Chong 2013;Sadia 2011) of m-commerce adoption.…”
Section: Factors Affecting Adoption Of M-commercementioning
confidence: 96%
“…Social influence has been found to be both a determinant (Lu 2014;Wei et al 2009) and an antecedent (Chan and Chong 2013;Sadia 2011) of m-commerce adoption. Similar findings on the effect of social influence on m-commerce adoption can be found in studies by Bhatti (2007), Chan and Chong (2013), Chong et al (2012), Khalifa and Cheng (2002), Lu (2014), Min et al (2008) and Wei et al (2009). Therefore, we propose the following hypotheses:…”
Section: Factors Affecting Adoption Of M-commercementioning
confidence: 96%
See 1 more Smart Citation
“…We strongly believe that with the widespread deployment of wireless technologies, the m-commerce will replace the paradigm of electronic business. With this in mind, several studies wondered the role of top m-commerce design to accommodate a certain usage behavior [23][24][25]. Therefore, this study is being carried out to determine the effect of m-commerce design usability on customers' trust.…”
Section: M-commercementioning
confidence: 99%
“…La tecnología móvil constituye en nuestros días un hecho social. La utilización de dispositivos móviles en las compras es percibida por los individuos como un signo de estatus (Hsu et al, 2007), y la influencia del grupo en la decisión de adoptar este canal está ampliamente contrastada (Gu et al, 2009;Lu, 2014 móviles luchan por destacar con la publicidad la idea que la utilización del dispositivo móvil es consistente con los valores y necesidades de los potenciales clientes (Chen, 2008), buscando representar la afinidad del dispositivo con la vida de los potenciales clientes (Bigné et al, 2007). En este sentido, es interesante resaltar las ventajas que reporta a ambas partes de la relación el marketing de permiso y la integración del comercio móvil en el CRM de la empresa (el denominado Mobile-Crm) (Awasthi y Sangle, 2012).…”
Section: El Comercio Móvil B2c: La "B" (Business)unclassified